2023
DOI: 10.3390/ma16072672
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Mechanical Properties between SMA Fiber and ECC Matrix under Direct Pullout Loads

Abstract: SMAF-ECC material composed of shape memory alloy fiber (SMAF) and engineered cementitious composite (ECC) has good bending and tensile properties, as well as good crack self-healing ability, energy consumption, and self-centering ability. The bond behavior between fiber and matrix is crucial to the effective utilization of the superelasticity of SMAF. The experimental study considered three variables: SMA fiber diameter, fiber end shape, and bond length. The pullout stress–strain curve of SMAF was obtained, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous investigations primarily examined the effects of fiber shape, cementitious, and ECC matrix on the bond slip characteristics of superelastic SMA fibers in cementitious ECC mixtures. [25,26,[33][34][35][36][37]. However, comprehensive and systematic investigations of the pullout behavior in SMA Fiber-Reinforced Engineered Cementitious Composite (SMAF-ECC) matrices are notably limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations primarily examined the effects of fiber shape, cementitious, and ECC matrix on the bond slip characteristics of superelastic SMA fibers in cementitious ECC mixtures. [25,26,[33][34][35][36][37]. However, comprehensive and systematic investigations of the pullout behavior in SMA Fiber-Reinforced Engineered Cementitious Composite (SMAF-ECC) matrices are notably limited.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao Yang et al [19] showed that when SMA fibers are effectively anchored in the ECC matrix, the superelastic characteristics of SMA fibers can be fully utilized, providing a flagshaped hysteretic energy dissipation capacity for SMAF-ECC beams and providing recovery force for composite material beams during unloading, enabling the beam to achieve selfclosing of cracks and self-recovery of deflection. Meanwhile, Zhao Yang et al [20] found that by setting up the end-knotted form of fibers, the SMAF-ECC half-dog bone specimens were subjected to direct drawing tests, and it was concluded that the knotted-end form could effectively improve the bonding performance between SMA fibers and ECC matrix, which provided the basic conditions for making full use of the superelasticity of SMA materials. In addition, Zhao Yang et al [21] conducted uniaxial cyclic tensile tests to investigate the self-recovery performance of SMAF-ECC under cyclic tensile.…”
Section: Introductionmentioning
confidence: 99%